Company Performance Analysis: Leadership Style, Corporate Culture and Human Resource Development - Widodo, Djoko Setyo; Silitonga, P. Eddy Sanusi (International Review of Management and Marketing, 2017)
This study analyzed the influence of Leadership Style, Corporate Culture and Human Resource Development on Company Performance. The research method is quantitative research, using survey method. The population of this study amounted to 2844 employees residing in 6 retail companies spread across Indonesia. The sample size used Slovin method for 351 respondents. Sampling method done by random. Analyzer used Multiple Linear Regression, continued with partial test of hypothesis (t test) and simultaneously (F test) with alpha 5 percent. Data analysis tool with SPSS application 23.00. The result of this research is that Leadership Style, Corporate Culture and Human Resource Development have positive and significant influence to Company Performance either partially or simultaneously. From the results of determination analysis there are other factors that affect the Company's performance in addition to variables of Leadership Style, Corporate Culture and Human Resource Development. The better the Leadership Style, Corporate Culture and Human Resource Development will be the better Corporate Performance. Keywords: Leadership Style, Corporate Culture, Human Resource Development and Organization Performance. JEL Clasifications: M53, M54